Experimental and numerical analysis of a test rig for structural testing of a full-scale aircraft wing - Arhore, Edore G.; Ghasemnejad, Hessam; Dayyani, Iman; Xu, Yigeng; Halliburton, Richard; Hakon, Ian; Beckwith, James; Stanely, F.; Gaskell, J. (MDPI, 2026)
Complexities are involved in testing an aircraft structure, including its size, which is essential for determining cost and feasibility. This paper focuses on the novelty of investigating the use of a scaled-down version of a full-scale aircraft wing and a test rig to predict the test rig’s structural response to the wing’s loading condition, thereby improving design and modelling techniques for the test rig. This paper also presents a methodology for sizing the test rig and the aircraft wing to perform structural tests on the wing. Numerical and experimental models subjected to various load cases are compared. This study begins by justifying the use of finite element analysis (FEA) for relevant parts of the test rig. A detailed explanation of the sizing method and its overall effect on the test rig is also provided. The results indicate a substantial similarity between the numerical and experimental models with respect to the stresses and deformation of the test specimen.
Keywords: 40 Engineering; 4001 Aerospace engineering; similitude; dimensional analysis; structural test; aircraft wing; modal analysis